Trehalose alleviates neuropathological and motor behaviour deficits of a transgenic mouse model of Machado-Joseph disease - Paixão, Susana Manuel da Silva Letra Lopes (2015)
Dissertação de mestrado em Biotecnologia Farmacêutica, apresentada à Faculdade de Farmácia da Universidade de Coimbra